The effect of online time on students’ academic performance: A study of cycle 1 and cycle 2 students in Abu Dhabi, UAE government schools - Sharabassy, Nermin Hamed (2014)
The last few years have witnessed a rapid growth in technology all over the world. This growth is evident in the great increase of Internet use and the technological devices that have been invented and commonly used in a very short time. Using the Internet has become the main source of getting information in all fields of knowledge. The benefits of using the Internet are widely spread to include different aspects of life; communicating with friends, booking flights to any destination in the world, checking bank accounts, paying bills, and helping with any kind of educational needs such as doing homework or research, preparing for assignments , projects and final assessments. This study is focussed on the time students in cycle 1 and 2 of Abu Dhabi, UAE government schools are spending online, and how it is affecting their academic performance. This study will also investigate the effect of this online time on their academic achievement and the perceptions of teachers, parents and the students themselves on the impact of this online time on their academic achievement at school. The study also focuses on the various Internet activities that the students are busy working on, and if online time can be beneficial for them to do their homework, school projects, and to be prepared for their final assessments, or is it merely a tool to communicate with friends through various social networks to play games, check emails and be used for entertainment only. The findings of this study have suggested that online time has a positive effect on the students’ academic performance unless it has not been used wisely within good online time management at school and at home. Online time can be used as an interactive factor to enhance the learning process if it is used wisely in a way that can stimulate the students’ needs and attention.